Jal Brahmi for commercial cultivation in low-lying rice-wheat cropping systems - Saran, P L; Kalariya, K A; Meena, R P; Devi, Ganga (Indian Horticulture, 2023)
Farmers of central Gujarat face water logging problems, especially during the rainy season, which limits cultivation of traditional crops. Therefore, introduction of new crops, which are feasible as well as acceptable in such areas was required. Directorate has suggested the Jal Brahmi as a suitable medicinal plant for such areas to an innovative farmer interested in MAPs cultivation. Through a field level demonstration, we were able to convince farmers, which gave fruitful results under low lying troubled fields.